64.4L: Late‐News Paper: Symmetric Panel Stacking Design for Achieving 3mm Rolling Radius in Plastic‐based AMOLED Display. Issue 1 (June 2015) - Lee, Meng‐Ting; Wang, Cheng‐Liang; Chan, Chi‐Shun; Fu, Ching‐Chieh; Chen, Chung‐Chia; Lin, Kuan‐Heng; Huang, Wen‐Chung; Tsai, Chih‐Hung; Weng, Zai‐Xien; Chan, Chih‐Cheng; Lin, Yu‐Ling; Huang, Tzu‐Yu; et al.
Abstract : A 5" plastic‐based AMOLED panel with optimal structure and optical design was fabricated. The panel is designed to coincide the OLED/TFT layer with the neutral plane and limit the largest strain of the outmost part to be less than 1%. Its performance remained prominent after repeated rolled at 3mm radius.